The effects of stress inoculation training and goal-setting program on anxiety, subjective pain, and rehabilitation adherence of injured filipino athletes - Montano, Julian Ramos, III (Animo Repository, 2000)
This study examined the effects of Stress Inoculation Training and Goal-Setting Program in reducing the state anxiety and subjective pain levels of injured athletes and in enhancing their rehabilitation adherence. Purposive sampling was used involving 30 intercollegiate athletes from major universities in Metro Manila who were suffering from a less than a month-old soft tissue injury at the Grade II severity level. These athletes were assigned to Stress Inoculation Training, Goal-Setting Program, and Control Group. There were ten participants in each condition. Each treatment client received three to four hours of individual counseling of either of the psychological interventions understudy. An analysis of the pretest to posttest scores and the change index of both treatment conditions showed a significant decrease in state anxiety and subjective pain levels while the control group did not show any significant change. However, on the same dependent variables, no significant differences were found between the two treatment conditions. Again, on the Rehabilitation Adherence ratio of the treatment conditions, no significant difference were found, but both (treatment conditions) were significantly higher than that of the control group. Findings revealed that Stress Inoculation Training and Goal-Setting Program are effective psychological interventions for injured athletes in reducing their state anxiety and subjective pain levels and in enhancing their rehabilitation adherence.